Religious Freedom and the Law
1 online resource (244 pages)
Keywords: This volume presents a timely analysis of some of the current controversies relating to freedom for religion and freedom from religion that have dominated headlines worldwide. The collection trains the lens closely on select issues and contexts to provide detailed snapshots of the ways in which freedom for and from religion are conceptualized, protected, neglected, and negotiated in diverse situations and locations. A broad range of issues including migration, education, the public space, prisons and healthcare are discussed drawing examples from Europe, the US, Asia, Africa and South America. Including contributions from leading experts in the field, the book will be essential reading for researchers and policy-makers interested in Law and Religion.